Strukturen und Praxis der psychologischen Abteilungen in der onkologischen und diabetologischen Rehabilitation: Ergebnisse einer bundesweiten Befragung. - Reese, C.; Hübner, P.; Petrak, F.; Schmucker, D.; Weis, J.; Mittag, O. (Rehabilitation, 2016)
Objective: To study the structural frame conditions and the contents of psychological activity in oncological rehabilitation as well as in rehabilitation of patients with type 2 diabetes.Methods: We conducted a nationwide survey of psychological services in rehabilitation facilities treating oncological patients and patients with type 2 diabetes.Results: 71 (of 145) oncological and 21 (of 63) diabetological rehabilitation facilities participated in the survey. In both indication areas an average of 1.1 psychologists is in charge of 100 patients. Between some rehabilitation facilities, however, there are considerable differences concerning the psychologist/patient ratio (in oncological rehabilitation facilities: standard deviation (SD)=0.52; in diabetological rehabilitation facilities: SD=0.35). Moreover, there is large heterogeneity among rehabilitation facilities as to the percentages of patients obtaining psychological interventions and the way in which psychological services allocate their working time.Conclusion: The general set-up of psychological services in oncological and diabetological rehabilitation facilities (especially the low psychologist/patient ratio in many facilities) can partly be considered insufficient. The heterogeneity with respect to the structural frame conditions and practice of psychological services reveals the low degree of standardization of psychological activity in both indication areas.